Formation of Hybrid Magnetic Films Composed of Fe3O4 and Epoxy Resin by Inkjet Printing - Hwan Cho, Sung; Joon Yoon, Young; Nam, Joong-Hee; Yeon Cho, Kwang; Kim, Chang-Yeol; Tae Kim, Hyo; Kim, Jong-Hee (Asian Journal of Chemistry, 2014)
Hybrid magnetic films composed of Fe3O4 powders and epoxy resin were fabricated by inkjet printing process. Through the optimization of Fe3O4 ink and inkjet parameters, the Fe3O4 films were formed with the thickness from 5 to 100 μm. The film thickness could be adjusted by varying the solid content of Fe3O4 ink and repeating the number of inkjet printing of the Fe3O4 ink. To obtain a rigid magnetic film, epoxy resin was infiltrated into the Fe3O4 film and subsequently cured at 250 ºC. It was the confirmed that highly-packed Fe3O4 hybrid film could be formed without any macro-voids after epoxy resin infiltration. The magnetic permeability and loss of hybrid Fe3O4 films with different film thickness were measured and those values at 13.56 MHz were compared. Magnetic properties of inkjet-printed Fe3O4 hybrid film was improved as the film thickness increased. Magnetic permeability and loss of Fe3O4 hybrid film with 30 μm thickness were 9.9 and 5.9, respectively.